Enhancing gastric cancer conventional chemotherapy effects by triple angiokinase inhibitor nintedanib in preclinical models - Awasthi, Niranjan; Schwarz, Margaret A.; Kaurich, Quinn; Zhang, Changhua; Hilberg, Frank; Schwarz, Roderich E. (Frontiers in Oncology, 2023)
Background: Gastric adenocarcinoma (GAC) is the fourth leading cause of cancer death worldwide. Systemic chemotherapy is a preferred treatment option for advanced and recurrent GAC, but response rates and survival prolongation remain limited. Tumor angiogenesis plays a critical role in GAC growth, invasion and metastasis. We investigated the antitumor efficacy of nintedanib, a potent triple angiokinase inhibitor for VEGFR-1/2/3, PDGFR-/ and FGFR-1/2/3, alone or in combination with chemotherapy, in preclinical models of GAC. Methods: Animal survival studies were performed in peritoneal dissemination xenografts in NOD-/SCID mice using human GAC cell lines MKN-45 and KATO-III. Tumor growth inhibition studies were performed in subcutaneous xenografts in NOD/SCID mice using human GAC cell lines MKN-45 and SNU-5. The mechanistic evaluation involved Immunohistochemistry analyses in tumor tissues obtained from subcutaneous xenografts. In vitro cell viability assays were performed using a colorimetric WST-1 reagent. Results: In MKN-45 GAC cell-derived peritoneal dissemination xenografts, animal survival was improved by nintedanib (33%), docetaxel (100%) and irinotecan (181%), while oxaliplatin, 5-FU and epirubicin had no effect. The addition of nintedanib to docetaxel (157%) or irinotecan (214%) led to a further extension in animal survival. In KATO-III GAC cell-derived xenografts carrying FGFR2 gene amplification, nintedanib extended survival by 209%. Again, the addition of nintedanib further enhanced the animal survival benefits of docetaxel (273%) and irinotecan (332%). In MKN-45 subcutaneous xenografts, nintedanib, epirubicin, docetaxel and irinotecan reduced tumor growth (range: 68-87%), while 5-FU and oxaliplatin had a smaller effect (40%). Nintedanib addition to all chemotherapeutics demonstrated a further reduction in tumor growth. Subcutaneous tumor analysis revealed that nintedanib attenuated tumor cell proliferation, reduced tumor vasculature and increased tumor cell death. Conclusion: Nintedanib showed notable antitumor efficacy and significantly improved taxane or irinotecan chemotherapy responses. These findings indicate that nintedanib, alone and in combination with a taxane or irinotecan, has the potential for improving clinical GAC therapy.